P27Kip1 and human cancers: A reappraisal of a still enigmatic protein. (10th September 2017) - Bencivenga, Debora; Caldarelli, Ilaria; Stampone, Emanuela; Mancini, Francesco Paolo; Balestrieri, Maria Luisa; Della Ragione, Fulvio; Borriello, Adriana
Abstract: p27 Kip1 is a cell cycle regulator firstly identified as a cyclin-dependent kinase inhibitor. For a long time, its function has been associated to cell cycle progression inhibition at G1/S boundary in response to antiproliferative stimuli. The picture resulted complicated by the discovery that p27 Kip1 is an intrinsically unstructured protein, with numerous CDK-dependent and -independent functions and involvement in many cellular processes, such as cytoskeleton dynamics and cell motility control, apoptosis and autophagy activation. Depending on the cell context, these activities might turn to be oncogenic and stimulate cancer progression and metastatization. Nevertheless, p27 Kip1 role in cancer biology suppression was underscored by myriad data reporting its down-regulation and/or cytoplasmic relocalization in different tumors, while usually no genetic alterations were found in human cancers, making the protein a non-canonical oncosuppressor. Recently, mostly due to advances in genomic analyses, CDKN1B, p27 Kip1 encoding gene, has been found mutated in several cancers, thus leading to a profound reappraisal of CDKN1B role in tumorigenesis. This review summarizes the main p27 Kip1 features, with major emphasis to its role in cancer biology and to the importance of CDKN1B mutations in tumor development. Highlights: We report the major structural features and roles of p27 Kip1 focusing on its characteristic of being an intrinsically unstructured protein. Numerous pieces of evidence have correlated a decrease or a cellular mislocalization of p27 Kip1 and the development of human tumors. Recent data have demonstrated that CDKN1B, the gene encoding p27 Kip1, is mutated in several human cancers.